2022
DOI: 10.3389/fmed.2022.1040654
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of burden of hospital-acquired pneumonia among abdominal surgical patients in tertiary university hospital in Serbia: A matched nested case-control study

Abstract: BackgroundIn the population of abdominal surgical patients hospital-acquired pneumonia (HAP) significantly increases morbidity and mortality.Patients and methodsThrough regular hospital surveillance of patients who received abdominal operations, we identified postoperative HAP from 2007 to 2019. In an initial nested case-control study, every surgical patient with HAP was compared with three control patients without HAP. Control patients were matched to the cases by age, gender, the American Society of Anesthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…However, it needs to be a concern for working staff that the finding of this bacteria in the air in the intensive care room needs special attention because several reports state that the finding of Acinetobacter baumanii, which is a bacterium that lives in moist environmental conditions and is an opportunistic bacterium that is commonly found in hospital or healthcare settings, is included in particular concern, especially when it is found in the community because of its natural resistance to antibiotics and its ability to experience high antibiotic resistance. Resistance to this bacterium is associated with a low immune system of infected patients or in ICUs with cases such as ventilator-associated pneumonia (VAP) or hospital-acquired pneumonia (HAP), skin and soft tissue infections, surgical site infection (SSI), bloodstream infections and CAUTI in patients treated in the ICU (32)(33)(34). Some studies reported that one of the most drug-resistant and clinically significant microorganisms in ICUs worldwide, antimicrobialresistant Acinetobacter baumannii, was found in dust on air conditioning vents, especially β-lactamase and carbapenem-producing strains in ICUs.…”
Section: Discussionmentioning
confidence: 99%
“…However, it needs to be a concern for working staff that the finding of this bacteria in the air in the intensive care room needs special attention because several reports state that the finding of Acinetobacter baumanii, which is a bacterium that lives in moist environmental conditions and is an opportunistic bacterium that is commonly found in hospital or healthcare settings, is included in particular concern, especially when it is found in the community because of its natural resistance to antibiotics and its ability to experience high antibiotic resistance. Resistance to this bacterium is associated with a low immune system of infected patients or in ICUs with cases such as ventilator-associated pneumonia (VAP) or hospital-acquired pneumonia (HAP), skin and soft tissue infections, surgical site infection (SSI), bloodstream infections and CAUTI in patients treated in the ICU (32)(33)(34). Some studies reported that one of the most drug-resistant and clinically significant microorganisms in ICUs worldwide, antimicrobialresistant Acinetobacter baumannii, was found in dust on air conditioning vents, especially β-lactamase and carbapenem-producing strains in ICUs.…”
Section: Discussionmentioning
confidence: 99%